Determining suitability for active recreation in agroforestal areas using spatial multicriteria analysis. Orienteering in Tejo International National Park - Quinta-Nova, L.C. (2016)
The growing demand for rural areas for tourist and recreational purposes, with special focus on areas of higher landscape value, requires the need to reconcile the enjoyment of these areas with the preservation and conservation of natural values. Thus arose the need to develop a methodology of land use management supported by multicriteria spatial analysis tools. To determine the areas with suitability for the practice of active recreational activities, it was used biophysical and socioeconomic data, that allowed the characterization of the territory and its use by different stakeholders. On the other hand, it was analyzed information on the specifics of a nature sport in order to identify the constraints and potentials for your practice. As a result we obtained a Suitability Map for Orientation of the Tejo International Natural Park (PNTI) in order to support their sustainable management.